Tourism in an uncertain world: Profiling the asean-bound leisure traveller - Loh, Jacqueline Po-Lin (2004)
Tourism is one of fastest growing and most important industries for many developing nations, including those in ASEAN. During the last two decades, ASEAN tourism has flourished mainly due to the increased affluence of international travellers and favourable exchange rates relative to tourist generating countries. ASEAN’s popularity as a leisure destination has also blossomed as seasoned travellers look beyond their traditional vacation spots, to explore new and exotic regions. Discriminating consumers who desire “something different” are turning away from those traditional tourism centers because of overdevelopment. To capitalize on the growing demand for their tourism products, ASEAN Governments and tour operators have invested heavily in facilities like luxurious resorts, golf courses, and theme parks to draw in institutionalized mass tourists. Unfortunately, tourism demand is highly vulnerable to national and regional uncertainties. With the advent of incidents like SARS and Bird Flu outbreaks; regional haze; Abu Sayyaf and Jemaah Islamiah terrorism; the Bali bombings; and political and religious insurgencies; ASEAN as a region is increasingly being painted This study challenges the current wisdom of targeting ASEAN-bound leisure travellers simply as if they belonged to one homogeneous group of mass tourists. This approach is unsustainable in the long-run, especially since mass tourists are the most likely to avoid an ASEAN perceived to be risky. Using a sample of 240 Singapore leisure travellers, respondents were classified according to Cohen’s 4 tourist roles, based on their respective risk perception levels and international travel attitudes. The quantitative results, complemented by findings from in-depth interviews, showed that differences in risk-profiles and travel attitudes influence travellers’ propensities, to visit or avoid particular vacation destinations. In addition, the findings highlight non-institutionalizedtravellers as a lucrative alternative market segment to institutionalized mass tourists.by the international media as a high-risk location.